Cervicogenic and Vestibular Vertigo-Bridging the Gap - Aditya Ranja; Shraddha Jain; Shyam Jungade (Journal of Clinical and Diagnostic Research, 2021)
The diagnosis and management of vertigo is still a challenge. Vertigo is managed by heterogenous group of specialists, including Otolaryngologists, Neurologists and Physiotherapists. The cause of vertigo could be vestibular, central or cervicogenic. The current review was undertaken as an attempt to highlight the various gaps in knowledge about vertigo of varied aetiologies. Cervicogenic vertigo is caused due to neck pathologies and is considered by some authors to be one of the most common vertigo syndromes. However, there is little mention of it in otolaryngology textbooks. Barriers across the specialties and lack of communication between the specialists are an impediment in vertigo management. This review has attempted to highlight the likely multifactorial aetiologies and fallacies in the pathophysiology of Meniere’s disease. The clinical overlaps in cervicogenic and vestibular vertigo have been discussed, some of them being, the occurrence of aural symptoms and neck pain in both the entities. This review article brings out the need to revisit the pathophysiology of vestibular vertigo syndromes and include cervicogenic dizziness in the list of vertigo syndromes in Otolaryngology textbooks. The authors found a dire need of an interdisciplinary approach to elucidate the cause of vertigo of varied presentation with the goal of better patient management.